Exploration And Identification Of Antagonic Fungi On The Rhizosphere Of Clove Plants (Syzygium aromaticum L.) In Ambon Island - Agustina Widiyanti; Jogeneis Patty; Gratiana N.C Tuhumury (Agrologia, 2022)
Antagonistic fungi are a group of fungi that can suppress or inhibit the growth and development of plant pathogens.  This study aimed to isolate the fungus from the rhizosphere of the clove plant (Syzygium aromaticum L.) from two sub-districts of Leihitu Barat and Leihitu, and to test the ability of these isolates to inhibit Rizoctonia solani.  Exploration was carried out using the simple random sampling method, taking rhizosphere soil samples from clove plants from Hatu, Allang, Asilulu and Seith.  Then isolated by the dual culture method after that, identified based on the identification key book and calculated its inhibition against plant pathogens. The results showed that 10 fungal isolates were identified, namely 4 fungal genera, namely Trichoderma, Aspergillus, Penicillium and Rhyzopus.  The soil around the rhizosphere of clove plants contains antagonistic fungi that can inhibit the growth of tomato sprouting pathogens (Rhizoctonia solani).  Obtained 7 isolates of the antagonist fungus Trichoderma sp. with the results of the antagonism test showing the highest inhibition was achieved by isolates of TrichoRCTAL2 (89,52%), and the lowest percentage was by isolates of TrichoRCTAS4 (44,07%).